Implementation of Social Rehability Program in Empowering Persons With Disabilities by the Social Service and Community Empowerment of Gorontalo City - Hasim, Zulkifli; Rachman, Ellys; Bakari, Luthfia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to analyze the role of MSMEs in empowering the local community economy and their contribution to improving the local economy. This study uses a qualitative descriptive method by collecting data through observation, interviews, and documentation. The focus of this study includes skills, limited capital, and innovation, products that are still the main obstacles in contributing MSMEs in Molangga Village. The results of the study show that empowering MSMEs has a positive impact on creating jobs , increasing community income, and encouraging economic independence. However, limited capital and minimal innovation are challenges that require further support, both from the government and related institutions. This study is expected to be a reference for developing policies that support the empowerment of MSMEs and improving the economic welfare of people in rural areas.